Evaluasi Kesesuaian Lahan Untuk Tanaman Jagung (Zea Mays L.) dan Ubi Jalar (Ipomoea batatas L.) di Kecamatan Kualuh Selatan Kabupaten Labuhanbatu Utara - Aslan Pasaribu; Zulkifli Nasution; Mariani Sembiring (Jurnal Agroekoteknologi, 2018)
This study aims to evaluate the suitability of corn crop plant (Zea mays L.) and sweet potato (Ipomea batatas L.) in South Kualuh Subdistrict of North Labuhanbatu District. The method used in this research is survey method From the results of the overlay from the map of soil types, map of topography, and map of height place, retrieved 5 units of land use map. SPL 1 has an area of ​​34.95 hectares, SPL 2 has an area of ​​12.96 hectares, and SPL 3 has an area of ​​24.96 hectares, SPL 4 has an area of ​​159.85 hectares, and SPL 5 has an area of ​​73 hectares. The result at this research showed the highest potential of land suitability classes in set of land 1 is corn (S2 tc) and sweet potato (S2 tc, wa), in set of land 2 is corn (S2 tc) and sweet potato (S2 tc, wa), in set of land 3 is corn (S2 tc) and sweet potato (S2 tc , wa), in in set of land 4 is corn (S2 tc) and sweet potato (S2 tc, wa), in set of land 5 is corn (S2 tc) and sweet potato (S2 tc, wa).